Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated Euro - Brüggemann, Wolfgang; Bergmann, Michael; Nierbauer, Kai-Uwe; Pflug, Ellen; Schmidt, Carlo; Weber, Daniel (Trees, 2009)
In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efﬁciency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the ﬁeld and reacted towards frost periods with the phenomenon of ‘‘chronic photoinhibition’’, i.e. a decrease in pre-dawn Fv/Fm and an increase in the deepoxidation state of the xanthophylls. Under dark and warmer conditions (room temperature), winter-acclimated leaves of the evergreen taxa except for Q. 9 turneri produced zeaand antheraxanthin and decreased Fv/Fm, possibly by creation of a chlororespiratory pH-gradient. It is suggested that the ability for dark violaxanthin deepoxidation may contribute to the winter hardiness of the evergreen taxa.
Keywords: á downregulation of ps; chlororespiration; chlororespiration á photoinhibition á; downregulation of ps II; ii; photoinhibition; Quercus; quercus á winter acclimation; winter acclimation